SoK: Delegated Security in the Internet of Things - Emiliia Geloczi; Felix Klement; Patrick Struck; Stefan Katzenbeisser (Future Internet)
The increased use of electronic devices in the Internet of Things (IoT) leads not only to an improved comfort of living but also to an increased risk of attacks. IoT security has thus become an important research field. However, due to limits on performance and bandwidth, IoT devices are often not powerful enough to execute, e.g., costly cryptographic algorithms or protocols. This limitation can be solved through a delegation concept. By delegating certain operations to devices with sufficient resources, it is possible to achieve a high level of security without overloading a device that needs protection. In this paper, we give an overview of current approaches for security delegation in the context of IoT, formalise security notions, discuss the security of existing approaches, and identify further research questions. Furthermore, a mathematical formalisation of the CIA triad (confidentiality, integrity, and availability) is proposed for the predefined application areas, in order to evaluate the different approaches.